2003
DOI: 10.2105/ajph.93.8.1253
|View full text |Cite
|
Sign up to set email alerts
|

Should the Centers for Disease Control and Prevention’s Childhood Lead Poisoning Intervention Level Be Lowered?

Abstract: The US Centers for Disease Control and Prevention (CDC) in 1991 chose 10 micro g/dL as an initial screening level for lead in children's blood. Current data on health risks and intervention options do not support generally lowering that level, but federal lead poisoning prevention efforts can be improved by revising the follow-up testing schedule for infants aged 1 year or less with blood lead levels of 5 micro g/dL or higher; universal education about lead exposure risks; universal administration of improved,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 71 publications
0
34
0
2
Order By: Relevance
“…Despite the accumulating data, CDC and some policy makers believe that CDC should retain the current 10 μg/dL blood lead standard (Bernard, 2003). They argue that a program targeted at levels below 5 μg/dL offers little benefit for the increased costs that would be incurred.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the accumulating data, CDC and some policy makers believe that CDC should retain the current 10 μg/dL blood lead standard (Bernard, 2003). They argue that a program targeted at levels below 5 μg/dL offers little benefit for the increased costs that would be incurred.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the increase in the auditory threshold was correlated with the levels of lead in blood 12,[13][14][15] while others did not confirm this finding 16,17 . Only a single study considered the cumulative lead level, given by the index calculation of the long term exposure to the metal, similar to that proposed in this study.…”
Section: Discussionmentioning
confidence: 96%
“…The Centers for Disease Control (CDC) estimate that 24 million houses with lead paint still exist in the United States, at least 4 million of which are inhabited by young children (CDC, 2004b). Not surprisingly, the families living in such houses are predominantly lower-income, members of minority groups, or both (National Research Council, 1993;Lamphear, Weitzman et al, 1996;Bernard, 2004).…”
Section: "Kennedy Krieger Cannot Understand How a Study Funded By Thementioning
confidence: 99%